The legend of Mar Qardagh : narrative and Christian heroism in late antique Iraq - Walker, Joel Thomas, 1968- (Berkeley : University of California Press, 2006)
Explores the history of Christianity in Iraq. This study uses an early seventh-century Christian martyr legend to elucidate the culture and society of late antique Iraq. It introduces a hero of epic proportions whose characteristics confound simple classification.
5. Remembering Mar Qardagh: The Origins and Evolution of an East-Syrian Martyr CultEpilogue: The Festival of Mar Qardagh at Melqi; Appendix; Select Bibliography; Index.
Includes bibliographical references and indexes.
Print version record.
English.
JSTOR
Keywords: Qardagh, -- Mar; Tašʻítā d-Mārí Qardag sāhdā.; Assyrian Church of the East -- Iraq -- History; Qardagh, -- Mar; Assyrian Church of the East; Tašʻítā d-Mārí Qardag sāhdā; Iraq -- Church history; Religion; Religion; Iraq; Religion; religion (discipline); RELIGION -- Christianity -- History; HISTORY -- Ancient -- General; Religion; Iraq; Teologi -- Teologi; Church history; History